2018
DOI: 10.1101/490417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MinION Nanopore Sequencing of Multiple Displacement Amplified Mycobacteria DNA Direct from Sputum

Abstract: 37Sequencing of pathogen DNA directly from clinical samples offers the possibilities of rapid 38 diagnosis, faster antimicrobial resistance prediction and enhanced outbreak investigation. The 39 approach is especially advantageous for infections caused by species which grow very slowly 40 in culture, such as Mycobacteria tuberculosis. Since the pathogen of interest may represent as 41 little as 0.01% of the total DNA, enrichment of the input material for target sequences by 42 specific amplification and, or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Partial sequencing was achieved for the direct repeat region from contaminated drinking trough water. While previous studies have shown it possible to undertake whole genome sequencing of pure isolates as well as partial sequencing and assembly of M. tuberculosis from low complexity human sputum samples (George et al, 2018), this is the first study to present a feasible method for resolving a degree of strain level differentiation directly from environmental reservoirs of infection. It is likely that the incomplete spoligotyping of contaminated drinking tough water is due to the low level of M. bovis within the sample which indicates that this strain typing tool is less sensitive than the qPCR method to identify and quantify M. bovis in environmental samples (King et al, 2015, Courtenay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Partial sequencing was achieved for the direct repeat region from contaminated drinking trough water. While previous studies have shown it possible to undertake whole genome sequencing of pure isolates as well as partial sequencing and assembly of M. tuberculosis from low complexity human sputum samples (George et al, 2018), this is the first study to present a feasible method for resolving a degree of strain level differentiation directly from environmental reservoirs of infection. It is likely that the incomplete spoligotyping of contaminated drinking tough water is due to the low level of M. bovis within the sample which indicates that this strain typing tool is less sensitive than the qPCR method to identify and quantify M. bovis in environmental samples (King et al, 2015, Courtenay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies exclusively used Oxford Nanopore Technologies (ONT) MinION. 26,29,32,39 Six studies compared the use of Illumina sequencing versus ONT MinION. 3,[21][22][23]31,37 Five studies sequenced on the ION Torrent/Proton.…”
Section: Methodology: Controlsmentioning
confidence: 99%
“…5,8,20,25,41,43,44 In other studies (n=13) there was no description of how the presence of an organism was confirmed. 19,[21][22][23]26,[31][32][33][34]36,37,45,46 Some studies (n=9) determined contamination without the use of a reported negative control by identifying known pathogens manually as described above (Figure 4). 3,20,22,[26][27][28][29]34,50 Therefore, by use of negative controls and other approaches, 26/36 (72%) studies report contamination of some degree while 9/36 (25%) studies had no details of contamination available.…”
Section: Assessing True Species Presence Versus Contaminationmentioning
confidence: 99%
“…Antibiotic resistance [7], Ebola [47], gonorrhea [23], West Nile virus, Zika [26], meningitis [6], tuberculosis [19], sepsis…”
Section: Infectionmentioning
confidence: 99%